Plant-soil-water relations in three contrasting environments - Gass, Tobah M., author; Binkley, Dan, advisor; Bauerle, William L. (William Leonard), 1972-, committee member; Knapp, Alan K., 1956-, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2010)
The relationships among soil nutrients, water availability, and vegetation can be studied over spatial and temporal scales that vary by orders of magnitude. Each provides a particular set of insights into tightly linked ecosystem dynamics. I examined the effects of rainfall on soil CO2-C efflux in a semi-arid woodland, the ramifications of ungulate herbivory for soil nutrients and microbial processes in a montane riparian zone, and the consequences of manipulating soil nutrient levels and vegetation density for carbon isotope discrimination in a wet tropical forest. Soil CO2-C efflux responded more strongly to a natural change in the timing and magnitude of precipitation that occurred during the study than to irrigation or drought treatments, indicating the importance of the timing of rainfall. Soil CO2-C efflux declined with artificial drought under trees and in open locations; the patterns and rates of the response differed between the two locations. Maximum efflux rates under trees occurred with supplemental irrigation; maximum rates in open locations occurred with ambient rainfall and artificial warming. Soil nutrient concentrations and quantities were significantly less than in paired plots that have been protected from grazing for 15 years. Low levels of nutrients were associated with higher bulk density and lower soil moisture in the grazed areas. Carbon isotopes from wood cellulose of trees in an experimental wet tropical forest were invariant across treatments, contrasting with significant treatment-related differences in gross primary production. I consider several reasons why discrimination might not co-vary with gross primary production, including decreased isotopic response when conductance is not limiting and the muting of signals in wood as compared to foliage. Each experiment reflected at least three years of treatment effects and included data ranging from the temporally and spatially integrated values of carbon isotopes from wood-tree rings and annual soil CO2-C efflux to the point processes captured by measurements of microbial biomass and fatty acids. Together, they demonstrate various sensitivities to environmental modifications that should increase our understanding of plant-soil-water relationships.
Keywords: soil respiration; soil nitrogen; grazing; drought; carbon isotope; Soil respiration; Carbon -- Isotopes; Soil ecology; Soils -- Nitrogen content; Plant-soil relationships; Plant-water relationships